OPTIMASI ALGORITMA K-MEANS TERHADAP DATA OUTLIER MENGGUNAKAN ROBUST DALAM SEGMENTASI PELANGGAN BIZNET MEDAN - Dwina Pri Indini; Solly Ariza; Zulham Sitorus (Smart Education, 2026)
Abstract: The massive growth of internet penetration in Indonesia has created competitive competition among internet service providers (ISPs), including Biznet Medan. However, the highly diverse and heterogeneous characteristics of customers make one-size-fits-all marketing strategies ineffective and inefficient. Processing large customer data for segmentation is often hampered by the presence of outliers, such as extreme income variations, which can disrupt the clustering accuracy of conventional algorithms. This study aims to optimize the K-Means algorithm in segmenting Biznet Medan's target market to maintain accuracy despite outliers, allowing the company to design more targeted marketing strategies. To overcome K-Means' sensitivity to outliers, this study applies the Robust Scaling technique. This solution uses the Median and Interquartile Range (IQR) values ​​instead of the mean, so that the cluster center points (centroids) remain stable and are not distorted by extreme data values. The research flow includes data collection of prospective Biznet Medan customers, data pre-processing (cleaning and scaling), feature selection (income, distance, and network requirements), and implementation of the K-Means model. Cluster quality evaluation is carried out by comparing the results of using StandardScaler and RobustScaler through the Silhouette Score and Davies Bouldin Index (DBI) metrics. The implementation successfully formed two main segments: Cluster 0 (Enterprise/Premium Customers) with high income characteristics and large bandwidth requirements (>200 Mbps), and Cluster 1 (Casual/Economical Customers) who dominate the market with lower network requirements (<50 Mbps). Optimization with Robust showed significant improvements in the evaluation metrics, where the Silhouette Score increased from 0.3133 to 0.6023, and the DBI value improved from 1.1421 to 0.8007. The implementation of Robust Scaling is effectively able to handle outlier problems in the K-Means algorithm, resulting in a more robust, efficient, and representative cluster structure. These results contribute to the processing of customer data for more objective strategic decision-making in ISP market expansion. Keywords: k-means; clustering; outlier; robust scaling; customer segmentation. Abstrak: Pertumbuhan internet di Indonesia yang masif telah menciptakan persaingan kompetitif di antara penyedia jasa internet (ISP), termasuk Biznet Medan. Namun, karakteristik pelanggan yang sangat beragam dan bersifat heterogen membuat strategi pemasaran satu untuk semua (one-size-fits-all) menjadi tidak efektif dan tidak efisien. Data calon pelanggan yang besar sering ditemui data yang hilang, perbedaan nilai data yang ekstrim sehingga pengolahan data calon pelanggan untuk segmentasi sering kali terkendala oleh adanya data pencilan (outlier) yang dapat mengganggu akurasi pengelompokan pada algoritma konvensional. Penelitian ini bertujuan untuk mengoptimasi algoritma K-Means dalam melakukan segmentasi target pasar Biznet Medan agar tetap akurat meskipun terdapat data outlier, sehingga perusahaan dapat merancang strategi pemasaran yang lebih tepat sasaran. Untuk mengatasi sensitivitas K-Means terhadap pencilan, penelitian ini menerapkan teknik Robust Scaling. Solusi ini menggunakan nilai Median dan Interquartile Range (IQR) sebagai pengganti rata-rata, sehingga titik pusat klaster (centroid) tetap stabil dan tidak terdistorsi oleh nilai data yang ekstrem. Alur penelitian meliputi pengumpulan data calon pelanggan Biznet Medan, pra-pemrosesan data (pembersihan dan scaling), pemilihan fitur (penghasilan, jarak, dan kebutuhan jaringan), serta implementasi model K-Means. Evaluasi kualitas klaster dilakukan dengan membandingkan hasil penggunaan StandardScaler dan RobustScaler melalui metrik Silhouette Score dan Davies Bouldin Index (DBI). Implementasi berhasil membentuk dua segmen utama: Cluster 0 (Pelanggan Enterprise/Premium) dengan karakteristik penghasilan tinggi dan kebutuhan bandwidth besar (>200 Mbps), serta Cluster 1 (Pelanggan Casual/Hemat) yang mendominasi pasar dengan kebutuhan jaringan lebih rendah (<50 Mbps). Optimasi dengan Robust menunjukkan peningkatan signifikan pada metrik evaluasi, di mana Silhouette Score meningkat dari 0,3133 menjadi 0,6023, dan nilai DBI membaik dari 1,1421 menjadi 0,8007. Penerapan Robust Scaling secara efektif mampu menangani masalah outlier pada algoritma K-Means, menghasilkan struktur klaster yang lebih kuat, efisien, dan representatif. Hasil ini memberikan kontribusi pada pengolahan data pelanggan untuk pengambilan keputusan strategis yang lebih objektif dalam ekspansi pasar ISP. Kata kunci: K-Means; klasterisasi; data pencilan; Robust Scaling; Segmentasi Pelanggan.